Dermatomyositis-like skin changes in a 5-year-old girl suffering from Lyme disease. - Abeck, D.; Altekrüger, I.; Segnini-Torres, M.; Willig, D.; Mensing, H.; Ring, J. (European Journal of Pediatric Dermatology, 2018)
The case of a five-year-old girl is presented, whose initial diagnosis according to the characteristic skin symptoms and systemic complaints was dermatomyositis. Since this diagnosis could not be confirmed by laboratory investigations, additional detailed enquiry led to the information of tick bites acquired eight weeks before. Therefore, an infection with Borrelia burgdorferi was suspected to be the origin, which could be confirmed by positive laboratory findings. Lumbar puncture finally led to the diagnosis of disseminated Lyme disease. This case is reported in order to emphasize the difficulties of achieving the correct diagnosis in cases of disseminated Lyme Borreliosis and stresses the importance of adeguate therapy.